Development of enhanced selective media for detection of Vibrio parahaemolyticus in oysters - Yoon, Jae-Hyun; Bae, Young-Min; Song, Hana; Lee, Soyul; Moon, Sung-Kwon; Oh, Se-Wook; Lee, Sun-Young (Food science and biotechnology, 2021)
This study was undertaken to develop enhanced selective media for detection of Vibrio parahaemolyticus in oysters. Primarily, tryptic soy agar (TSA) was supplemented with 4.5–5% NaCl, 0.1–0.5% oxgall, and/or 1–2% sodium citrate, and adjusted to pH 8–9. A total of 21 Vibrio spp., 24 indicators, and 26 food-borne isolates were streaked on the modified media, followed by 24 h of incubation at 37 °C. While all the indicators and isolates failed to grow on TSA containing 5% NaCl, 0.5% oxgall, and 2% sodium citrate (TSA OSS1 ; pH 9), V. parahaemolyticus was culturable on this selective medium. Particularly, the ability of TSA OSS1 to quantify V . parahaemolyticus in oysters was superior to thiosulphate citrate bile salts sucrose (TCBS) agar. V. parahaemolyticus distinctly produced its white-yellowish, round, and edge-pointed colony on TSA OSS1 . TSAO SS1 with high selectivity potentials over TCBS may be a promising alternative for detection of V . parahaemolyticus in seafoods or natural reservoirs.